Malaysians’ intention to invest in stock market: Moderator of financial literacy - Boey, Liang Jing; Chua, Wei Yang; Ooi, Shyuan Chee; Wong, Kang Jun (2025)
This research explores how subjective norms, self-efficacy, perceived risk, and personality traits shape Malaysians’ interest in stock market investing, while also considering the role of financial literacy as a moderating factor. The research gathered responses from 387 individuals across different states in Malaysia, with data analysed with descriptive analysis, scale measurement, and inferential analysis. The results indicate that subjective norms and personality traits have the strong impact on investment decisions, while self-efficacy and perceived risk affect it not so strong. The result also show that the financial literacy enhances the effects of subjective norms and personality traits but does not significantly alter the influence of self-efficacy or perceived risk. These findings highlighted the importance of improving financial education, especially for those interested in investing but uncertain about their decisions. The insights from this research may help policymakers and financial professionals to develop more effective investment awareness programs